(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
This article deals with the problem of interconnection between the contact taboos as a form of communicative taboos and Ukrainians’ mystic, religion and mythological beliefs on the material of M. Kotsubynsky’s “Shadows of Forgotten Ancestors”.